Multi-objective optimization for the green vehicle routing problem: A systematic literature review and future directions - Júlio César Ferreira; Maria Teresinha Arns Steiner; Osíris Canciglieri Junior (Cogent Engineering, 2020)
This article aims to present research conducted on the literature regarding multi-objective optimization for routing problems with environmental considerations, referred to here as Multi-objective Optimization for the Green Vehicle Routing Problem (MOOGVRP). A Brazilian database, CAPES (Coordination for the Improvement of Higher Education Personnel), was used to collect articles of general application, case studies and reviews in English starting from, since 2012. The terms “green vehicle routing problem” (GVRP), “pollution routing problem” (PRP), “vehicle routing problem in reverse logistics” (VRPRL) and “multi-objective” were used in the research protocol. Consequently, this study obtained 1,744 research results that, following the application of the filtering criterion, resulted in a sample of 76 articles from 38 journals, for which a bibliometric data (bibliometric review) survey was conducted. The originality of this article lies in how the research is presented, highlighting the results and details obtained through the survey, which may be considered of great academic importance in the sense of guiding the trends for future research.